PENGARUH METODE PENGUKURAN INTELLECTUAL CAPITAL BERBASIS PASAR DAN NILAI TAMBAH TERHADAP KINERJA PASAR DAN KINERJA KEUANGAN PERUSAHAAN (Studi Kasus Pada Perusahaan Manufaktur yang Terdaftar di BEI Tahun 2007-2011) - Aty Utami; Fuad Fuad (Diponegoro Journal of Accounting, 2013)
The purpose this study is to compare measurement approach of intellectual capital by market based and efficiency of value added and investigate the association between intellectual capital to corporate market performance and three profitability dimensions of financial company’s performance: ROA, ROE, and EPS. This study used quantitative method on financial statement of manufactures listed in Indonesia Stock Exchange during 5 years period from 2007 until 2011. Three hundred and ninety four companies were collected using purposive sampling method in this study.It is empirical study using PLS for the data analysis. The findings show that : IC which measured by market based influences positively to corporate market performance and financial company’s performance. The other method of IC measured by value added intellectual coefficient- VAIC influences positively to corporate market value and financial company’s performance. For comparison between measurement approach of IC, VAIC more accurate for investigate the association between IC and corporate market performance and financial company’s performance rather than market based approach.